Recognition of a Baby's Emotional Cry towards Robotics Baby Caregiver. (1st February 2013) - Yamamoto, Shota; Yoshitomi, Yasunari; Tabuse, Masayoshi; Kushida, Kou; Asada, Taro
We developed a method for pattern recognition of baby's emotions (discomfortable, hungry, or sleepy) expressed in the baby's cries. A 32-dimensional fast Fourier transform is performed for sound form clips, detected by our reported method and used as training data. The power of the sound form judged as a silent region is subtracted from each power of the frequency element. The power of each frequency element after the subtraction is treated as one of the elements of the feature vector. We perform principal component analysis (PCA) for the feature vectors of the training data. The emotion of the baby is recognized by the nearest neighbor criterion applied to the feature vector obtained from the test data of sound form clips after projecting the feature vector on the PCA space from the training data. Then, the emotion with the highest frequency among the recognition results for a sound form clip is judged as the emotion expressed by the baby's cry. We successfully applied the proposed method to pattern recognition of baby's emotions. The present investigation concerns the first stage of the development of a robotics baby caregiver that has the ability to detect baby's emotions. In this first stage, we have developed a method for detecting baby's emotions. We expect that the proposed method could be used in robots that can help take care of babies.